HIGH AVIAN SPECIES RICHNESS IN A MINUTE CERRADO REMNANT IN SOUTHEASTERN BRAZIL - Victor Rodrigues Antonelli; Renata Cristina Batista Fonseca; Carlos Otávio Araujo Gussoni; Lorena Patrício Silva; Silvia Mitiko Nishida; Vagner Cavarzere (Revista do Instituto Florestal)
The Cerrado is the most diverse tropical savanna in the world, and it is threatened due to land conversion for agriculture and urban expansion. We inventoried the birds in Botucatu State Forest (FEB), a 33-ha legally protected (but without good management) Cerrado remnant in southeastern Brazil, to evaluate its potential for the creation of a totally protected reserve. We conducted monthly visits to the area from 2019 to 2020 (with additional sporadic observations from 2018 to 2024) and searched for bird records provided by the literature and online ornithological platforms. We compared the presence of Cerrado species to another 14 protected cerrado areas in the state while accounting for area size with a Bayesian logistic regression model. An Unweighted Pair Group Method with Arithmetic Mean was employed to analyze the hierarchical relationships among species based on their dissimilarities. Area size did not account for differences in species richness, but Itirapina Ecological Station was the only remnant that showed higher probabilities of harboring more birds than FEB, which clustered with very large (> 2,000 ha) remnants. We found that of the 251 species mentioned for FEB and surroundings, three are Cerrado endemics and four are globally Vulnerable. Nonetheless, because this small area is as speciose as protected and larger grasslands, and because it is one of the last strongholds for threatened grassland physiognomies and as many as 13 threatened bird species at state level, we strongly recommend that FEB be declared an integrally protected reserve, thereby gaining proper management under Brazilian legislation.